Pioglitazone prevents the endothelial dysfunction induced by ischemia and reperfusion in healthy subjects - Sakatani, Yuka; Miyoshi, Toru; Oe, Hiroki; Noda, Yoko; Ohno, Yuko; Nakamura, Kazufumi; Saito, Yukihiro; Osawa, Kazuhiro; Morita, Hiroshi; Kohno, Kunihisa; Ito, Hiroshi (Journal of cardiovascular pharmacology, 2014)
No study has investigated whether pioglitazone (an agonist of peroxisome proliferator-activated receptor gamma) protects against ischemia and reperfusion (IR)-induced endothelial dysfunction in humans. In the first crossover study, 20 volunteers were randomized to 1 week of pioglitazone (30 mg/d, postoperatively) or control (no treatment). In the second single-arm study, 15 volunteers received pioglitazone and the cyclooxygenase-2 inhibitor meloxicam for 1 week. On day 7, endothelium-dependent flow-mediated dilation (FMD) of the distal brachial artery was measured before and after IR (15 minutes of ischemia followed by 15 minutes of reperfusion in the proximal upper arm). Pre-IR brachial-artery diameter and FMD were similar across the 2 sessions (control, pioglitazone) in protocol 1 and between the 2 protocols. IR significantly blunted FMD after no treatment (pre-IR FMD: 10.2% ± 2.6%; post-IR FMD: 3.5% ± 1.9%, P < 0.01) but not after pioglitazone administration (pre-IR FMD: 9.7% ± 2.5%; post-IR FMD: 8.8% ± 2.9%, P = 0.11). This protective effect was accompanied by an increase in serum levels of the antioxidant enzyme extracellular superoxide dismutase and was not affected by concomitant administration of the cyclooxygenase-2 inhibitor meloxicam (P = 0.10). In humans, pioglitazone provides potent protection against IR-induced endothelial dysfunction.